(untitled) (Kinesiology, 2022)
The purpose of this study was to examine the load of regular players and floater players in a specific small-sided game. Twenty semi-professional soccer players performed one 4vs4+2, modifying the position of the floaters (internal, external, zone, square and without floaters). Total distance covered, distance covered at speeds between 7-13.9 km·h−1, 14-17.9 km·h−1, and ≥18 km·h−1, accelerations and decelerations between 2.5-4 m·s−2, maximal and mean heart rate (HR) and rating of perceived exertion (RPE) were analyzed. Internal floaters achieved greater total distance covered, accelerations and RPE than in any other position. Internal and external floaters achieved more distance covered at 7-13.9, 14-17.9, >18 km·h-1 and HR than zone and square floaters. With internal floaters, regular players covered more distance covered >18 km·h-1 than in any other 4vs4+2 format, and with internal and external floaters regular players covered greater total distance and distance at 14-17.9 km·h-1 than without floaters or with zone or square floaters. Regular players showed greater total distance covered, distance covered at 7-13.9, 14-17.9, >18 km·h-1, accelerations and RPE than floaters in all 4vs4+2. These data showed that floater position in 4vs4+2 game influenced the internal and external load of both the regular players and the floaters. Key words: football, time-motion, global position system (GPS), heart rate, rate of perceived exertion